Effect of Corporate Governance And Disclosure of Corporate Social Responsibility on The Quality of Financial Statements - Winda Pramudita Rusady; Andrian Budi Prasetyo (Universitas Trunojoyo Madura, 2018)
The aim of this study was to analyze the effect of the disclosure of corporate social responsibility on the quality of the financial reports and the disclosure of corporate social responsibility mediation on the financial report quality of corporate governance. The dependent variable, financial report quality, was measured by earnings management (RAM); while, the independent variables, corporate social responsibility disclosure and corporate governance, were measured byCSRindex andCGIindex. Meanwhile, the control variables were the negative value of operating cash flow, profit, debt ratio, market volatility, and operating cycle. The sample was manufacturing companies listed in Indonesia Stock Exchange in the period of 2013-2015. The sampling method was purposive sampling and the technique of analysis was multiple linear regression. The results showed that corporate social responsibility disclosure significantly and negatively affectedRAMand the mediation of corporate social responsibility disclosure on the effect of corporate governance did not affect the quality of the financial reports.